2018
DOI: 10.21873/invivo.11153
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Gamma System Irradiation: A Promising Treatment for Low-grade Brainstem Gliomas

Abstract: Brainstem gliomas account for about 20% of primary brain tumors in children and for <2% of gliomas in adult patients (1-3). Gliomas of the brainstem are most commonly located in the pons, but are also found in the mesencephalon, the cerebellar peduncles or the medulla oblongata (4). A tumor located in the brainstem can be associated with severe clinical or even life-threatening symptoms, since this part of the brain regulates motion functions, as well as respiratory and circulatory functions. Such tumors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…So we did not include these 61 patients in the data set so as to make reliable conclusion. Given that the surgical experience is growing and efforts are made to attempt preferable adjuvant therapy methods (16,(33)(34)(35), the present study based on cases reported between 2004 and 2015 could not capture the most updated clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…So we did not include these 61 patients in the data set so as to make reliable conclusion. Given that the surgical experience is growing and efforts are made to attempt preferable adjuvant therapy methods (16,(33)(34)(35), the present study based on cases reported between 2004 and 2015 could not capture the most updated clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in stereotactic imaging and computer software further enhanced treatment planning and responsiveness (3,4). In the current neuro-oncology era, GKRS is frequently considered as upfront and adjuvant treatment in combination with surgical resection, or as a minimally invasive alternative in patients not eligible to surgery (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%